1996
DOI: 10.1042/bj3170395
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry and cluster specificity of copper binding to metallothionein: homogeneous metal clusters

Abstract: Experiments were done to define the stoichiometry of binding of Cu(I) to metallothionein (MT) and to determine its sites of binding in mixed-metal species. Spectrophotometric titrations of rabbit liver Cd7-MT 2, apoMT, and Cd4-alpha-domain with Cu(I) revealed endpoints of 3-4, 4 and 8, and 4 and 6-7 added Cu(I)/mol of MT for the three species respectively. Observed endpoints depended on conditions of the titration and the wavelength chosen for absorbance measurement. Nevertheless, from metal and sulphydryl ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…Polymeric clustering of heavy metals with low molecular weight sulphur-rich proteins (such as metallothionein) and segregation into vesicles have been proposed as mechanisms for this type of bioaccumulation in bacteria. 49 It has been shown that L. plantarum has a nutrient dependent manganese transporter, which may account for the presences of intracellular Cd. However, due to the low amount of intracellular Cd (but not Pb) compared with the extracellular bound heavy metals, we consider cell binding of heavy metals to be the primary mechanisms of heavy metal sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric clustering of heavy metals with low molecular weight sulphur-rich proteins (such as metallothionein) and segregation into vesicles have been proposed as mechanisms for this type of bioaccumulation in bacteria. 49 It has been shown that L. plantarum has a nutrient dependent manganese transporter, which may account for the presences of intracellular Cd. However, due to the low amount of intracellular Cd (but not Pb) compared with the extracellular bound heavy metals, we consider cell binding of heavy metals to be the primary mechanisms of heavy metal sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 18 metals are able to associate with MT, but Zn 2+ is only able to be displaced by Cu + , Cd 2+ , Pb 2+ , Ag + , Hg 2+ and Bi 2+ (4). MT comprises two subunits: The more stable α-domain (C-terminal), which incorporates four divalent metal atoms, and the β-domain (N-terminal), which contains only three divalent metal ions and is more reactive (5). MT exchange ability depends upon the metal species present, and the majority of MTs exist in zinc form or as mixed-metal proteins in vivo (6).…”
Section: Introductionmentioning
confidence: 99%
“…From the high concentration factor determined here it is reasonable to assume that at least metallothionein-like polypeptides are present in sponges; furthermore it can be suggested that these proteins have different associ.ation constants to heavy metals, which are apparently lower (numerically) for zinc than for cadmium. It is known from vertebrates that zinc bound to metallothionelns can be displaced by cadmium (Chen et al 1996).…”
Section: Discussionmentioning
confidence: 99%